A Review of the Biomechanical Differences Between the High-Bar and Low-Bar Back-Squat. Issue 9 (September 2017) - Glassbrook, Daniel J.; Helms, Eric R.; Brown, Scott R.; Storey, Adam G.
Abstract : Abstract: Glassbrook, DJ, Helms, ER, Brown, SR, and Storey, AG. A review of the biomechanical differences between the high-bar and low-bar back-squat. J Strength Cond Res 31(9): 2618–2634, 2017—The back-squat is a common exercise in strength and conditioning for a variety of sports. It is widely regarded as a fundamental movement to increase and measure lower-body and trunk function, as well as an effective injury rehabilitation exercise. There are typically 2 different bar positions used when performing the back-squat: the traditional "high-bar" back-squat (HBBS) and the "low-bar" back-squat (LBBS). Different movement strategies are used to ensure that the center of mass remains in the base of support for balance during the execution of these lifts. These movement strategies manifest as differences in (a) joint angles, (b) vertical ground reaction forces, and (c) the activity of key muscles. This review showed that the HBBS is characterized by greater knee flexion, lesser hip flexion, a more upright torso, and a deeper squat. The LBBS is characterized by greater hip flexion and, therefore, a greater forward lean. However, there are limited differences in vertical ground reaction forces between the HBBS and LBBS. The LBBS can also be characterized by a greater muscle activity of the erector spinae, adductors, and gluteal muscles, whereas the HBBS can be characterized by greater quadriceps muscle activity. Practitioners seeking to develop the posterior-chain hip musculature (i.e., gluteal, hamstring, and erector muscle groups) may seek to use the LBBS. In comparison, those seeking to replicate movements with a more upright torso and contribution from the quadriceps may rather seek to use the HBBS in training.